Stress Hyperglycemia Does Not Affect Clinical Outcome of Diabetic Patients Receiving Intravenous Thrombolysis for Acute Ischemic Stroke - Merlino, Giovanni; Pez, Sara; Tereshko, Yan; Gigli, Gian Luigi; Lorenzut, Simone; Surcinelli, Andrea; Valente, Mariarosaria (Frontiers in Neurology, 2022)
Although stress hyperglycemia represents a main risk factor for poor outcome among patients with acute ischemic stroke (AIS) undergoing recanalization therapy, we have limited information regarding a possible influence of the premorbid diabetic status on this association. We recruited consecutive patients admitted to the Udine University Hospital with AIS who were treated with intravenous thrombolysis (IVT) from January 2015 to September 2020. On the basis of the premorbid diabetic status, our sample was composed of 130 patients with and 371 patients without diabetes. The glucose-to-glycated hemoglobin ratio (GAR) was used to measure stress hyperglycemia. Patients were stratified into 3 groups by tertiles of GAR (Q1–Q3). The higher GAR index was, the more severe stress hyperglycemia was considered. Among diabetic patients we did not observe any significant association between severe stress hyperglycemia and outcome measures (three-month poor outcome: Q1, 53.7%; Q2, 53.5%; Q3, 58.7%; p = 0.854; three-month mortality: Q1, 14.6%; Q2, 9.3%; Q3, 23.9%; p = 0.165; symptomatic intracranial hemorrhage: Q1, 7.3%; Q2, 14%; Q3, 19.6%; p = 0.256). Differently, non-diabetic subjects with more severe stress hyperglycemia showed a higher prevalence of three-month poor outcome (Q1, 32.2%; Q2, 27.7%; Q3, 60.3%; p = 0.001), three-month mortality (Q1, 9.1%; Q2, 8.4%; Q3, 18.3%; p = 0.026), and symptomatic intracranial hemorrhage (Q1, 0.8%; Q2, 0.8%; Q3, 9.9; p = 0.001). After controlling for several confounders, severe stress hyperglycemia remained a significant predictor of three-month poor outcome (OR 2.1, 95% CI 1.03–4.28, p = 0.041), three-month mortality (OR 2.39, 95% CI 1.09–5.26, p = 0.029) and symptomatic intracranial hemorrhage (OR 12.62, 95% CI 1.5–106, p = 0.02) among non-diabetics. In conclusion, premorbid diabetic status seems to influence outcome in AIS patients receiving IVT. Indeed, odds of functional dependency, mortality and hemorrhagic complications were significantly increased in patients with more severe stress hyperglycemia only when they were not affected by diabetes.